2017
DOI: 10.1080/14767058.2017.1384806
|View full text |Cite
|
Sign up to set email alerts
|

Twin transvaginal cervical length at 16–20 weeks and prediction of preterm birth*

Abstract: In an asymptomatic twin population, a single transvaginal cervical length between 16 and 20 weeks was not predictive of spontaneous preterm birth before 34 weeks. Thus, our findings suggest that routine transvaginal cervical length screening of twins should not be performed between 16-20 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Many studies have used cervical length, cervical elastography or cervical consistency index to identify singleton pregnancy at risk of PTD. In twin pregnancies, most studies have focused on cervical length as a predictor for PTD [ 18 , 40 43 ], very few have used cervical SWE as a tool to investigate the predictive effect of cervical changes on PTD. Ono et al reported that SWE is a helpful tool for measuring the changes in cervical stiffness in 254 singleton pregnancies and 26 twin pregnancies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have used cervical length, cervical elastography or cervical consistency index to identify singleton pregnancy at risk of PTD. In twin pregnancies, most studies have focused on cervical length as a predictor for PTD [ 18 , 40 43 ], very few have used cervical SWE as a tool to investigate the predictive effect of cervical changes on PTD. Ono et al reported that SWE is a helpful tool for measuring the changes in cervical stiffness in 254 singleton pregnancies and 26 twin pregnancies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various methods have been suggested for predicting PTD in twin pregnancies, and transvaginal cervical length (TVCL) measurement in the second trimester has been shown to help predict spontaneous PTD [ 15 17 ]. However, the major limitation of using cervical length alone in the second trimester is its low sensitivity and positive predictive value for PTD [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, approaches used in singleton pregnancies to attenuate the risk of preterm birth have not been widely successful in multiple gestations. 12 13 14 15 Despite these potential differences, a prior preterm birth seems to confer a similarly increased risk for preterm birth in twins. 16 17…”
mentioning
confidence: 99%
“…11 Moreover, approaches used in singleton pregnancies to attenuate the risk of preterm birth have not been widely successful in multiple gestations. [12][13][14][15] Despite these potential differences, a prior preterm birth seems to confer a similarly increased risk for preterm birth in twins. 16,17 In contrast, the protective role a previous term delivery may play in attenuating the risk of spontaneous preterm birth is less well defined.…”
mentioning
confidence: 99%
“…An a priori total sample size of 57 was calculated, of 38 controls and 19 cases. At the time of setting up the study, no twin CCI data was available, and the sample size was based upon a previous publication of CCI in high-risk singletons [10] that noted an AUC for CL of 0.51 and CCI of 0.73 and keeping account for the wide variety of AUCs published for the prediction of PTB in twins using CL [23,24]. This calculation included a type I error of 0.05, power of 0.90 with an allocation ratio of 2 and an anticipated sPTB rate of >20%.…”
mentioning
confidence: 99%